Utilisation of Youtube as a Video-based Learning Media - Rachman, Azhariah; Emer, Souza; Pangaribuan, Jontra Jusat; Ole, Anita Amelia; Wati, Indah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The world of education and teaching is a part that cannot be separated from technological devices and the internet, educators utilizing this technology is very helpful for learning development. Therefore, this study aims to determine the utilization of Youtube as a video-based learning media. To find out the extent to which this video-based learning media is utilized, a survey was conducted to 50% of teachers who teach at high schools in Solok City by giving a questionnaire about the utilization of Youtube as a video-based learning media at the school. This type of research was conducted using descriptive quantitative. And the object of this research is educators and students at high schools in Solok City. And this data collection technique uses observation techniques using online questionnaires and online-based in-depth interviews. The results of this study are to find out if Youtube as a video-based learning media is very helpful for educators in learning development.